The Afrotropical genus Rhinolaetia Schouteden, 1965 and its systematic position within Scutelleridae (Hemiptera: Heteroptera) - Czaja, Joanna (Zootaxa, 2016)
The monotypic Afrotropical genus Rhinolaetia Schouteden, 1865 (Hemiptera: Heteroptera: Scutelleridae) is redescribed. The head, wings, female genitalia and habitus of Rhinolaetia overlaeti Schouteden, 1965 are illustrated. Morphological features of Rhinolaetia and selected representatives of six scutellerid subfamilies are listed and compared. The systematic position of this genus is briefly discussed. Close affinity of Rhinolaetia overlaeti with representatives of subfamilies Odontotarsinae and Odontoscelinae is observed.